Edukasi Pencegahan Demam Berdarah Dengue (DBD) pada Siswa SMA Negeri 3 Kendari - Muchtar, Febriana; Lestari, Hariati; Effendy, Devi Savitri; Bahar, Hartati; Tosepu, Ramadhan; Ahmad, La Ode Ali Imran (UKInstitute, 2022)
Dengue hemorrhagic fever or known as DHF is an infectious disease caused by the dengue virus through the bite of the Aedes aegypti mosquito. Dengue fever is very susceptible to occur in residential conditions that do not care about environmental cleanliness. This can be caused by a lack of knowledge and application of clean and healthy living behavior (PHBS). The purpose of the community service activity is to provide information about the prevention of dengue hemorrhagic fever to students of SMA Negeri 3 Kendari. The counseling was carried out using the lecture method, question and answer and discussion. The toolkit used a leaflet from the Ministry of Health of The Republic of Indonesia. The service activities were enthusiastically followed by the students and they were committed to implementing clean and healthy living behavior as an effort to prevent dengue hemorrhagic fever. Abstrak. Demam berdarah dengue atau yang dikenal dengan DBD merupakan penyakit infeksi yang disebabkan oleh virus dengue melalui gigitan nyamuk Aedes aegypti. Penyakit demam berdarah sangat rentan terjadi pada kondisi pemukiman yang tidak peduli dengan kebersihan lingkungan. Hal ini dapat disebabkan karena kurangnya pengetahuan dan penerapan tentang perilaku hidup bersih dan sehat (PHBS). Tujuan kegiatan pengabdian adalah untuk memberikan informasi tentang pencegahan demam berdarah dengue pada siswa SMA Negeri 3 Kendari. Penyuluhan dilakukan dengan metode ceramah, tanya jawab dan diskusi. Penyuluhan menggunakan leaflet Kemenskes RI. Kegiatan pengabdian diikuti dengan antusias oleh siswa-siswi dan mereka berkomitmen untuk menerapkan perilaku hidup bersih dan sehat sebagai upaya pencegahan demam berdarah dengue.